A system dynamics approach for assessing SMEs' competitiveness - Lafuente, Esteban; Szerb, László; Rideg, András (Journal of small business and enterprise development, 2020)
PurposeThe analysis of the interconnectedness between resources and capabilities, and the way businesses use them as competitive weapons is a central element of the strategic management literature. Finding the appropriate configuration of competitive pillars is particularly relevant for resource-constrained small businesses. Drawing on the resource-based view and the configuration theory, this study evaluates the effect of both competitiveness and the configuration of the competitiveness system on performance.Design/methodology/approachAn index methodology based on the configuration theory was used to compute the competitiveness index on a unique sample of 625 Hungarian small- and medium-sized firms. The study hypotheses were tested via regression analysis.FindingsResults show that the impact of competitiveness-enhancing strategies is conditional on the configuration of the system of competencies. Low-competitive businesses benefit more from investments in the weakest competitive pillar, while strategies oriented to improve more than one competitive pillar yield higher competitiveness improvements among high-competitive businesses. Our findings also indicate that competitiveness positively impacts performance, and that the exploitation of competitive strengths leads to superior results among high-competitive businesses.Originality/valueBy employing an index methodology, our analysis contributes to unveil how competitiveness impact business performance. The proposed analysis has value for scholars and strategy makers by showing how the configuration of the business' competitive system—in terms of competitive strengths and weaknesses—conditions the generally positive impact of competitiveness enhancing actions linked to the acquisition or development of resources and capabilities.